Students' Responses to The Ethno-SSI-Based Guided Inquiry Learning Model - Sa'idah, Zahirah Indana; Setiawan, Beni (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2026)
This study aims to describe students’ responses to the implementation of a guided inquiry learning model based on Etno-SSI. The research employed a quantitative, descriptive research design. The sample consisted of 25 students from class VIII-D, selected through purposive sampling. Data collection was carried out by distributing a response questionnaire administered after the implementation of the guided inquiry learning model based on Etno-SSI. The data were analyzed by calculating percentages for each questionnaire item, which comprised 12 items covering students’ active participation in the applied learning method, skill improvement, and students’ satisfaction with the learning process. The results showed that students’ responses to the implementation of the Etno-SSI-based guided inquiry learning model on nutrition material obtained an average score of 90, with an average indicator percentage of 87.15%, indicating very good performance. It can be concluded that the Etno-SSI-based guided inquiry learning model is capable of encouraging students’ active participation, improving their skills, and providing satisfaction in the learning process on nutrition material. Therefore, this model is suitable as an alternative for contextual and meaningful learning.